Peptide Markers for Rapid Detection of KPC Carbapenemase by LC-MS/MS - Honghui Wang (Nature Portfolio, 2017)
Abstract Carbapenemase producing organisms (CPOs) represent an urgent public health threat, and the need for new rapid methods to detect these organisms has been widely recognized. CPOs carrying the Klebsiella pneumoniae carbapenemase (bla KPC ) gene have caused outbreaks globally with substantial attributable mortality. Here we describe the validation of a rapid MS method for the direct detection of unique tryptic peptides of the KPC protein in clinical bacterial isolates with an isolate-to-result time of less than 90 minutes. Using a genoproteomic discovery approach that combines theoretical peptidome analysis and liquid chromatography-tandem MS (LC-MS/MS), we selected three high abundance peptide markers of the KPC protein that can be robustly detected following rapid tryptic digestion. Protein BLAST analysis confirmed that the chosen peptide markers were unique to KPC. A blinded validation set containing 20 KPC-positive and 80 KPC-negative clinical isolates, performed in triplicate (300 runs) demonstrated 100% sensitivity and 100% specificity (60/60 positive identifications, 240/240 negative identifications) using defined rules for positive calls. The most robust tryptic peptide marker in the validation was LTLGSALAAPQR. The peptide discovery and detection methods validated here are general and should be broadly applicable to allow the direct and rapid detection of other resistance determinants.